Linking Human Capital Resourcing Practices and Performance of Financial Cooperatives in Kenya: Does Presence of Formal Human Resource Department Matter?. (May 2019) - Mutua, Mbithi
Financial cooperatives are collectively one of the key drivers of Kenyan economy. Thus, this research sought to investigate the relationship between human capital (HC) resourcing practices and performance of these organizations. Performance as the dependent variable was conceptualized to have two dimensions, financial and non-financial. Data was collected from 340 financial cooperatives within Nairobi County. Simple random sampling technique was used in selecting organizations from where data was collected. Both interview and questionnaire methods were used to collect qualitative and quantitative data, respectively. The findings indicated that presence of formal HR department within an organization leads to better HC resourcing practices as compared to a situation where there is no formal HRM department. The study found a significant relationship between HC resourcing practices and performance of financial cooperatives. Further, the study recommends those organizations without formal HRM departments to create them. Additionally, so as to enjoy higher levels of performance and reduce labour turnover, financial cooperatives need to improve their HC resourcing practices.